When is vancomycin prophylaxis necessary? Risk factors for MRSA surgical site infection - Cynthia T. Nguyen; Rachel Baccile; Amanda M. Brown; Alison K. Lew; Jennifer Pisano; Natasha N. Pettit (Cambridge University Press, 2024)
Abstract Background: The 2022 SHEA/IDSA/APIC guidance for surgical site infection (SSI) prevention recommends reserving vancomycin prophylaxis to patients who are methicillin-resistant Staphylococcus aureus (MRSA) colonized. Unfortunately, vancomycin prophylaxis remains common due to the overestimation of MRSA risk and the desire to cover MRSA in patients with certain healthcare-associated characteristics. To optimize vancomycin prophylaxis, we sought to identify risk factors for MRSA SSI. Methods: This was a single-center, case-control study of patients with a postoperative SSI after undergoing a National Healthcare Safety Network operative procedure over eight years. MRSA SSI cases were compared to non-MRSA SSI controls. Forty-two demographic, medical, and surgical characteristics were evaluated. Results: Of the 441 patients included, 23 developed MRSA SSIs (rate = 5.2 per 100 SSIs). In the multivariable model, we identified two independent risk factors for MRSA SSI: a history of MRSA colonization or infection (OR, 9.0 [95% CI, 1.9-29.6]) and hip or knee replacement surgery (OR, 3.8 [95% CI, 1.3-9.9]). Hemodialysis, previous hospitalization, and prolonged hospitalization prior to the procedure had no measurable association with odds of MRSA SSI. Conclusions: Patients with prior MRSA colonization or infection had 9-10 times greater odds of MRSA SSI and patients undergoing hip and knee replacement had 3-4 times greater odds of MRSA SSI. Healthcare-associated characteristics, such as previous hospitalization or hemodialysis, were not associated with MRSA SSI. Our findings support national recommendations to reserve vancomycin prophylaxis for patients who are MRSA colonized, as well as those undergoing hip and knee replacement, in the absence of routine MRSA colonization surveillance.